Essays on cryptocurrencies and traditional assets in emerging market economies: dynamic modelling, connectedness, and spillovers - Omane-Adjepong, Maurice (My University, 2020)
The last decade has experienced notable changes and unique innovations in the global financial system. In particular, the introduction of cryptocurrencies, pioneered by Bitcoin and later other alternative coins (best known as altcoins) by libertarian cryptographers after several efforts in the 1990s to usher in electronic currencies foundered, has been lauded and likewise received enormous attention worldwide, raising many concerns for governments, monetary authorities and other regulatory bodies. Originally designed as electronic cash for decentralised peer-to-peer online financial transactions, secured by cryptographic algorithms, cryptocurrency, a specialised kind of digital currency, in barely a decade of existence, is challenged with an identity crisis. The debate as to what cryptocurrency is, or has become looms in the minds of the general public, and it has been the subject of media commentary. At the same time, the limited amount of research on the topic has only raised more questions than answers. For instance, not only are the existing studies not attacking the root of the deepest questions posed by the rise of cryptocurrencies to date, but also they are not robustly studied methodologically. The depth of analysis is shallow, and the scope of the studies published on the subject matter so far is very limited, both in space and time. Additionally, the extent of the relatedness of the new digital currency market to traditional assets, especially in frontier and emerging economies remains a virgin field. This naturally raises additional concerns: does the emergence of cryptocurrencies offer any relevant economic benefits to these emerging market economies? What implications does this evolution hold for established financial systems? Answers to these questions, and many more are crucial for monetary policy effectiveness, legislation and regulation, financial system stability, the future of cryptocurrencies, and overarchingly, to illuminate the blind spots of the enthusiastic libertarian public, as well as the general investor community. iii In light of the above, this thesis makes a bold attempt at addressing some of the weaknesses of extant research, extend the frontiers of knowledge in this new financial instrument, and shed insights on cryptocurrencies in emerging market economies, proxied by those in the G20. The study produced interesting juxtapositions in three essays. The first essay examined the evolving characteristics of cryptocurrencies under five sub-themes, and presents a map for analysing the cryptocurrency market. We find that Bitcoin and the largest long-lived altcoins are collectively unique instruments that share features of paper money, security assets (mostly equities), and commodity money (such as gold and oil), making the digital currencies a “trinity-hybrid” financial instrument which could best operate under the private sector to complement emerging currencies and assets. For emerging market economies, cryptocurrencies, in our view, is a three-in-one financial instrument, if and only if its role is limited to exchange of goods and services, and helping facilitate transactions of various kinds. This, in turn, raises a number of possibilities for recalibrating the current financial architecture while addressing the regulatory changes that ought to be in place for a well-functioning diversified economy. The second empirical essay found evidence in favour of an extremely weakly correlated market, and later, multifaceted economic benefits of cryptocurrency in times where emerging market economies’ assets wander in distress. This positions the new currency market to the advantage of heterogeneous groups of emerging market investors. However, we caution that expectations of such derived economic benefits need to be examined further on a case by case basis, and in a measured manner, especially given that the cryptocurrency market is still at its embryonic stages of evolution. iv The third and final essay allays the fears of investors and market participants, and reveals for the first time that the cryptocurrency market is less influenced by existing highly integrated instruments, and has little effect on emerging markets, and consequently pose, for now, a negligible danger. At their current level of development, some economies are not yet exposed to the variety of developments in the world of electronic commerce and payment systems that make the algorithms that power the peer-to-peer decentralised ledger platforms seamless. This may change in the future. For now, we are sure that the coming into being of cryptocurrencies is an inevitable consequence of the financial sector paradigms of the last few decades, however, the distributional consequences across regions, countries and among different market participants are largely asymmetric. The insights gleaned from this study, therefore, open doors for policymakers to properly fine-tune their economies to maximise the upside potential presented by this asset class and minimise the downside risks, in the light of what has been learned about the role of cryptocurrencies so far.
A thesis submitted in fulfilment of the requirement for the degree Doctor of Philosophy in Finance to the Faculty of Commerce, Law and Management, the Graduate School of Business Administration, University of the Witwatersrand, Johannesburg, 2020
Keywords: Cryptocurrency; Digital currency; Shock spillover; UCTD; SDG-8: Decent work and economic growth